Tweets from tahrir - Idle, Nadia; Nunns, Alex (Doha - =Bloomsbury-qatar foundation, 2011)
The Twitter accounts of the activists who brought heady days of revolution to Egypt in January and February this year paint an exhilarating picture of an uprising in real-time. Thousands of young people documented on cell phones every stage of their revolution, as it happened. This book brings together a selection of key tweets in a compelling, fast-paced narrative, allowing the story of the uprising to be told directly by the people in Cairo's Tahrir Square
Egyptʼs revolution as it unfolded, in the words of the people who made it
Many of those tweeting also took photographs with their phones and these illustrate the book, providing remarkable snapshots from the heart of the action
with a foreword by AHDAF SOUEIF
12
Keywords: Revelation; Social contract